2017
DOI: 10.1186/s13568-017-0470-6
|View full text |Cite
|
Sign up to set email alerts
|

Improving extracellular production of Serratia marcescens lytic polysaccharide monooxygenase CBP21 and Aeromonas veronii B565 chitinase Chi92 in Escherichia coli and their synergism

Abstract: Lytic polysaccharide monooxygenases (LPMOs) can oxidize recalcitrant polysaccharides and boost the conversion of the second most abundant polysaccharide chitin by chitinase. In this study, we aimed to achieve the efficient extracellular production of Serratia marcescens LPMO CBP21 and Aeromonas veronii B565 chitinase Chi92 by Escherichia coli. Twelve signal peptides reported with high secretion efficiency were screened to assess the extracellular production efficiency of CBP21 and Chi92, with glycine used as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…The half-saturating concentration of free CBP21 for binding to ␤-chitin is in the M range (14). It is well known that the binding affinity of CBP21 to ␣-chitin is much lower than that to ␤-chitin (15)(16)(17) Table S1. B, assessing the importance of the sequence of adding the various chemicals.…”
Section: Kinetics Of the H 2 O 2 -Driven Degradation Of Chitin By Cbp21mentioning
confidence: 99%
“…The half-saturating concentration of free CBP21 for binding to ␤-chitin is in the M range (14). It is well known that the binding affinity of CBP21 to ␣-chitin is much lower than that to ␤-chitin (15)(16)(17) Table S1. B, assessing the importance of the sequence of adding the various chemicals.…”
Section: Kinetics Of the H 2 O 2 -Driven Degradation Of Chitin By Cbp21mentioning
confidence: 99%
“…The newly formed chitin chain ends formed by LPMO activity, represent new points of attachment for the chitinases, thereby increasing substrate accessibility. Indeed, several studies have demonstrated this phenomenon (16, 6870), including a study on the virulence-related LPMO from Listeria monocytogenes (71).…”
Section: Discussionmentioning
confidence: 97%
“…As the co-culture required a freshwater salinity, we investigated the chitinolytic enzymes of A. hydrophila . In fact, an E. coli strain secreting a chitinase from A. hydrophila as well as an LPMO from S. marcescens proved that simultaneous production and secretion of these two types of enzymes by E. coli is possible (Yang et al 2017 ). We have identified the A. hydrophila strain AH-1 N based on an enrichment approach with chitin as substrate (Stumpf et al 2019 ), and characterized its chitinase AH-1NChi as being rather efficient on crystalline chitin, and as acting synergistically with the LPMO AhLPMO10A from the same strain (Vortmann et al unpublished).…”
Section: Discussionmentioning
confidence: 99%